Review of Lophotettix, the sole member of the subfamily Lophotettiginae Hancock, 1909 (Insecta: Orthoptera: Caelifera: Tetrigidae) - Silva, Daniela Santos Martins; Cadena-Castañeda, Oscar J.; Pereira, Marcelo Ribeiro; de Domenico, Fernando Campos; Sperber, Carlos Frankl (Zootaxa, 2019)
Lophotettiginae is a small, peculiar taxon of the Neotropical region, characterized mainly by median carina compresso-cristated or leaf-like crest, antennae flattened laterally and expanding from the base to the apex (incrassate shape). This subfamily has only one genus known as Lophotettix Hancock, 1909 that comprises five species. Here, we reviewed the types of the five known species, highlighting morphological aspects that distinguish the species from each other and from other tetrigids. Additionally, we also provide a pictorial identification key to Lophotettix species. Our results indicated that Lophotettiginae is a well-defined taxon and there are no synonyms among its species.